2017
DOI: 10.1039/c6sc04989c
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry in nanoconfined water

Abstract: Nanoconfined liquids have extremely different properties from the bulk, which profoundly affects chemical reactions taking place in nanosolvation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
169
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(172 citation statements)
references
References 60 publications
3
169
0
Order By: Relevance
“…The significant acceleration of reactions in confined environments has recently been reported in the literature (1)(2)(3)(4)(5)(6)(7). The reaction environments investigated span a diverse range, including charged microdroplets (1-3), microdiameter emulsions (5), inverted micelles (8), and the surfaces of aerosol particles (9).…”
mentioning
confidence: 94%
“…The significant acceleration of reactions in confined environments has recently been reported in the literature (1)(2)(3)(4)(5)(6)(7). The reaction environments investigated span a diverse range, including charged microdroplets (1-3), microdiameter emulsions (5), inverted micelles (8), and the surfaces of aerosol particles (9).…”
mentioning
confidence: 94%
“…[8][9][10] For example, a study focused on prebiotic peptide chemistry in water nanoconfined by mineral surfaces found that not only the energetics of the reactions, but also the reaction mechanisms, can be affected by nanoconfinement. 11 Recently, Zare et al and Cooks and co-workers have shown that many reactions can be accelerated in microdroplets, such as the spontaneous phosphorylation of sugars, production of ribonucleosides, and Diels-Alder chemistry. 6,[12][13][14][15] However, the underlying origin of the acceleration of the microdroplet remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Arrhenius (2003) considered the mineral as exhibiting "primitive cellular metabolic function." In this regard, it has been recently suggested that green rust and mackinawite, the objet trouvé at the ancient alkaline mounds, could have acted as the multitask protoenzymes, condensers, or nanoengines-the prebiological machinery-to enable the emergence of life (Russell and Nitschke, 2017;Muñoz-Santiburcio and Marx, 2017). Russell and Nitschke (2017) described a model whereby nitrate in the Hadean Ocean is reduced to nitric oxide, ammonia, and aminogen in the hydrated interlayers of green rust, fed with electrons from hydrothermal hydrogen.…”
mentioning
confidence: 99%